The therapeutic communication in relation nurse-user of basic care: an instrument for the promotion of health and citizenship - Jerusa Gomes Vasconcellos Haddad; Eliara Pilecco Machado; João Neves-Amado; Elma Lourdes i Campos Pavone Zobol (O Mundo da Saúde, 2011)
it is a methodological paper aiming to present the theoretical poles of the construction of an instrument for the observation of communication elements in Basic Care. It brings the Script for Observation of the Interpersonal Communication in the Infirmary Care, containing the elements that compose care, such as empathy, respect, receptive listening and support for the patient in its reflections. The instrument has been made to identify these elements in the dynamics of contact in the interface of the clinic nurse-user.